Inducing organizational citizenship behavior for the environment through sustainable human resource management practices: drawing implications for organizational sustainability in Pakistan's Textile Industry - Ms. Aimun Khawaja (Corresponding author),; Dr. Khalida Naseem Janjua, (Al-Qanṭara, 2024)
The environmental issue has turned out to be a new area of concern in the organization’s human resource management agenda, particularly in enhancing employees’ environmental conduct at the workplace. Therefore, organizational citizenship behavior toward the environment (OCBE) has been currently inspiring researchers in management. In line with the AMO theory, this study intends to assess the impact of sustainable practices on organizational sustainability through the construct of OCBE. To gather data from primary sources convenience sampling and purposive sampling methods were employed. The textile industries of Punjab where respondents are HR managers, operational managers, and other employees were used to generate the data for the research. This research employed the Smart PLS 4.0 software to analyze the results which were done using the structural equation modeling method. This research is unique in the context of Pakistan and speaks volumes of the importance of Sustaining HR practices for Organizational Sustainability. The research offers important implications for organizations in developing countries especially those operating in environmentally vulnerable regions such as Punjab, Pakistan on how to manage dreadful conditions in the environment.